1983
DOI: 10.1002/jbm.820170512
|View full text |Cite
|
Sign up to set email alerts
|

Macroporous hydrogel membranes for a hybrid artificial pancreas. I. Synthesis and chamber fabrication

Abstract: We report development of special macroporous semipermeable membranes and diffusion chambers made of polymerized 2-hydroxyethyl methacrylate (pHEMA), synthesized specifically to enclose living insulin-producing pancreatic islet cells for the treatment of diabetes. This material was selected to minimize the fibrotic encapsulation which has limited hybrid artificial pancreas efforts with other membranes, including Millipore and Nuclepore filters. The pore density and pore size distribution were dependent on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…5c and d due to the higher concentration of excess water in the structure compared to the 50% gel. These results agree with the studies of Ronel et al [42] in which they observed no pores for WCIPM below 50% and observed pores 5-10 m is size for WCIPM of 60%.…”
Section: Sem Imagessupporting
confidence: 95%
See 1 more Smart Citation
“…5c and d due to the higher concentration of excess water in the structure compared to the 50% gel. These results agree with the studies of Ronel et al [42] in which they observed no pores for WCIPM below 50% and observed pores 5-10 m is size for WCIPM of 60%.…”
Section: Sem Imagessupporting
confidence: 95%
“…[34]. There are also a number of studies in literature that have focused on studying the effect of water content on the polymerizing mixture on the material properties of p-HEMA hydrogels [35][36][37][38][39][40][41][42]. Also a large number of studies have focused on understanding and modeling release of solutes from hydrogels.…”
Section: Introductionmentioning
confidence: 97%
“…In 1983, macroporous HEMA membranes were used to form containers for the transplantation of pancreas tissue [78]. The goal was to enhance the transport of insulin while preventing ingrowth of leucocytes.…”
Section: Instructive Examples Of Liquid-liquid Two Phase Systemsmentioning
confidence: 99%
“…Therefore, also the polymer PDMAEMA was evaluated as an alternative polymer for gene delivery. This methacrylate polymer has excellent biocompatibility and is therefore an interesting alternative for biomedical purposes (Klomp et al, 1979;Ronel et al, 1983;Yasuda, 1975).…”
Section: Introductionmentioning
confidence: 99%